Similarity Score for the Identification of Active Sites in Patients With Atrial Fibrillation - Ravikumar, Vasanth; Thakare, Sanket; Kong, Xiangzhen; Roukoz, Henri; Tolkacheva, Elena G. (Frontiers in Physiology, 2022)
Atrial fibrillation (AF) is the most common cardiac arrhythmia and precursor to other cardiac diseases. Catheter ablation is associated with limited success rates in patients with persistent AF. Currently, existing mapping systems fail to identify critical target sites for ablation. Recently, we proposed and validated several individual techniques, such as dominant frequency (DF), multiscale frequency (MSF), kurtosis (Kt), and multiscale entropy (MSE), to identify active sites of arrhythmias using simulated intracardiac electrograms (iEGMs). However, the individual performances of these techniques to identify arrhythmogenic substrates are not reliable. Objective: This work aims to develop a similarity score using various iEGMs analysis techniques to more accurately identify the spatial location of active sites of arrhythmia in AF patients. Methods: Clinical bipolar iEGMs were obtained from AF patients that underwent either successful (m=4) or unsuccessful (m=4) catheter ablation. A similarity score (0 - 3) was developed via the earth mover’s distance approach based on a combination of DF, MSF, MSE, and Kt techniques. Results: Individual techniques successfully discriminated between successful and unsuccessful AF ablation patients but were not reliable in identifying active spatial sites of AF. However, the proposed similarity score was able to pinpoint the spatial sites with high values (active AF sites) that were observed only in patients with unsuccessful AF termination, suggesting that these active sites were missed during the ablation procedure. Conclusion: Arrhythmogenic substrates with abnormal electrical activity are identified in patients with unsuccessful AF termination after catheter ablation, suggesting clinical efficacy of similarity score.